Chapter Claudio Magris e il mondo nordico. Uno scambio fecondo - CULEDDU, Sara (Biblioteca di Studi di Filologia Moderna, 2021)
The current article is aimed to outline a first review of the solid relationship of Claudio Magris with the Nordic world, both from the perspective of his reception in Denmark, Norway and Sweden and from the study of his fecund encounter with the works of authors like Henrik Ibsen, Knut Hamsun, Bjørnstjerne Bjørnson, Jens Peter Jacobsen, Herman Bang and others. These authors, whose works were partially translated by Magris, eventually played a meaningful role in his own writing. Besides affirming himself as a relevant voice in the Scandinavian context, his work as a mediator for Nordic literature has made him a reference point for Scandinavian studies in our country.